Single-step aerosol synthesis of oxygen-deficient blue titania - Domaschke, Maximilian; Strunz, Lea; Peukert, Wolfgang (Chemical Engineering Science, 2019)
We present a novel approach for the single-step, continuous aerosol synthesis of blue, oxygen-deficient titania in a hot-wall reactor operated under reducing conditions by adding hydrogen. The precursor titanium(IV) tetraisopropoxide is evaporated in a bubbler and consecutively carried into the reactor by a nitrogen stream where it undergoes thermal decomposition. According to X-ray diffraction analysis, several reduced titania states, among them the Magneli phases Ti4O7 and Ti5O9, are formed via the intermediates anatase and rutile. By slight modifications in the reactor setup both nanoparticles in the size range from 20 to 50 nm with high surface area and well-defined spherical submicron particles of 100 to 160 nm diameter can be produced. In particular, crystallographically phase-pure Ti4O7 is formed at high reactor temperatures. The presented synthesis process is scalable and poses an attractive alternative for the multi-step synthesis of oxygen deficient titania nanoparticles that is currently done via batch-wise annealing. Such nanoparticles are attractive material in the field of photocatalysis. They can be used for both water splitting to produce hydrogen and the decomposition of organic pollutants. (C) 2019 Elsevier Ltd. All rights reserved.
CRIS-Team WoS Importer:2019-07-02